(untitled) (Historia, 2021)
At the age of thirteen, the author of this book, living in Germany, discovered that she had an African ancestor, who had been married to her great-great-great grandfather, the missionary Johann Heinrich Schmelen, who had worked for the London Missionary Society (LMS) in what is now Namibia and the Northern Cape in the early nineteenth century.